Pendayagunaan Zakat dalam Upaya Penanggulangan Kemiskinan Perspektif Al-Qur'an - Muhammad Sarjan; Achmad Abubakar; Halima Basri (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2022)
This study aims to analyze the utilization of zakat in an effort to reduce poverty from the perspective of the Koran. Where is Zakat as the third pillar of Islam, that paying zakat is an obligation for every Muslim to purify his wealth by distributing it to the needy and poor according to the criteria set by the Shari'a. The type of research used is qualitative research using thematic methods with a normative approach. The thematic method in question is to collect verses from the Qur'an from all suras related to the theme of poverty, both explicit and implicit. Then the normative review is intended to examine the perspective on zakat and its prevention of poverty based on the Qur'an. Collecting data through literature study on related verses of the Koran and analyzed qualitatively. This study found that Zakat is something that is obligatory for Muslims who can play an active role in poverty reduction through efforts to distribute Zakat to the poor. Furthermore, zakat management must be regulated professionally so that zakat does not only meet consumption needs but can also be managed as a source of income through the use of zakat as business capital and study costs for the poor. Recipients of zakat are not only objects of giving zakat but they must have a responsibility in using zakat as an effort to empower and develop themselves so that they can be independent and can make economic improvements to their families.